Studi evaluasi jalur pedestrian di Jalan Raya Modo, Kabupaten Lamongan - Nur Hidayatin Munawaroh; Irawan Setyabudi; Rizki Alfian (Prodi Arsitektur Lanskap, Fakultas Pertanian, Universitas Udayana, 2025)
The pedestrian track on Jalan Raya Modo is the sidewalk used by the community, usually they use it to go to public facilities such as markets, banks, government offices and schools. The bottom of the sidewalk also functions as a drainage. However, the pedestrian track on Jalan Raya Modo also has several problems, including the disconnection path, hardscape damage, land use change of the pedestrian track to selling area, parking, and gardening using pots. The purpose of this study is evaluating the hardscape and softscape elements on pedestrian track on Jalan Raya Modo and make a recommendation for pedestrian track by redesign concepts. The research was using the questionnaire method with random sampling of 90 respondents and Importance Performance Analysis, this analysis aims to measure the relationship betweenpedestrian track users and improved facilities. Based on the results, themain priority for improvement is add the crossing path, repair of sidewalkdamage, and addition the trash bins. The facilities that need to bemaintained are the addition of vegetation like the tree, shrub, andgroundcover, and also the plants that easy to maintain.